Syntactic Object Representations Found in Awgni Sentences - Berhanu Asaye Agajie (OKARA: Jurnal Bahasa dan Sastra, 2020)
Teachers and students in Injibara college were unable to understand syntactic object representations found in Awgni sentences. The motivation of this research was designed to fill the gap by analyzing syntactic object representations found in Awgni sentences. Henceforth, the objective of the study was to examine the Syntactic Object representations found within Awgni sentences classified by their function. A descriptive analysis was employed to interpret the sentence structures. The data were collected from the native speakers of Awi people (7 males, 6 females) based on their day-to-day outgoing acts, and from different texts. By purposive sampling, 23 sentences were selected, arranged, and described. The method of data analysis applied was Labeling Algorithm {XP, YP}. Thus, raising XP Syntactic Objects has been modified and consequently, there is only one visible head. The result indicated that Awgni sentences in terms of their forms, forming, a causal relationship they contain were different. On the other hand, each sentence structure shares Syntactic Object representations that include NPs, VPs, DPs, PPs, ADVPs, and APs. Finally, the study recommended further research on how (LA) {H, XP}, and {X, Y} works to describe the label of every Syntactic Object representations found within sentence structures in Awgni.